Clinical management of emerging sinonasal malignancies. Issue 8 (25th March 2020) - Contrera, Kevin J.; Woody, Neil M.; Rahman, Mobeen; Sindwani, Raj; Burkey, Brian B.
Abstract: Several emerging sinonasal malignancies have recently been described in the pathology literature. Although not all distinctly classified by the World Health Organization, these rare tumors present a management challenge to surgeons and oncologists. While prior studies have summarized histologic details, a clinically focused review is currently lacking in the literature. This review describes the presentation, histopathology, imaging, treatment, and prognosis of newly described or recently evolving sinonasal malignancies while highlighting the distinguishing features of these entities. It includes teratocarcinosarcoma, human papillomavirus‐related multiphenotypic carcinoma, biphenotypic sinonasal sarcoma, sinonasal renal cell‐like adenocarcinoma, NUT‐midline carcinoma, squamous cell carcinoma associated with inverted papilloma, sinonasal undifferentiated carcinoma, and INI‐1‐deficient sinonasal carcinoma. By describing the diagnosis, treatment, and prognosis of these recently defined entities, this clinical review aims to help guide oncologists in the clinical management of these patients.